Dono Imperiale La collezione mineralogica dell'Imperatore Giuseppe II al Collegio Nazareno di Roma - Franza, Annarita (Cataloghi e collezioni, 2023)
This volume presents the recovery, cataloging, and valorization project of the collection donated by the Holy Roman Emperor Joseph II (1741-1790) to the Mineralogical Cabinet of the Collegio Nazareno in Rome in 1785. This donation represents, so far, the only geo-mineralogical collection belonging to Joseph II with certainty. The specimen cataloging records, drawn according to the ICCD national catalographic standards for the mineralogical (BNM) and petrographic (BNPE) heritage, are freely available on the Catalogo Generale dei Beni Culturali website. The collection is open to visitors in its permanent exhibition at the Istituto San Giuseppe Calasanzio in Rome. This volume has been realized within the project PANN20.00605 "Dono imperiale. La collezione mineralogica dell'Imperatore Giuseppe II al Collegio Nazareno di Roma" thanks to the financial support of the Italian Ministry of University and Research, Annual Grant - Legge 6/2000 - D.D. 1524 of 21/01/2019.